Presupuesto de obra de una vivienda unifamiliar ubicada en el barrio Blanca García de Álvarez del Cantón Machala. - Pachala Ortíz , Vicente Alexander (My University, 2020)
In this research work, the information on each activity to be executed in the project is detailed and thus be able to prepare the work budget for a single-family house with two floors ground floor and upper floor, with a construction area of 215.11 m², implanted in an area of land of 141.84 m² in the Blanca García Álvarez neighborhood of the city of Machala. The purpose of this research work is to estimate the cost that a two-story single-family home should have, commit each activity to the work through the unitary method and thus be able to estimate the budget for our project. Also to carry out our project, it is necessary to know the technical specifications and construction regulations, in order to be able to adequately prepare the plans and to achieve our objective, it was necessary to use a Microsoft Excel computer tool since we It facilitated the calculation of our technical memory based on the plans and the designer and helped us organize each activity that was going to be carried out in each unit price analysis, managing to obtain each of our items and as a result obtain our approximate budget for the project. As a final result of our research work, we have that the budget for our two-story house located in the Blanca García Álvarez neighborhood is approximately ninety-nine thousand nine hundred and seventy-three dollars and 90/100 cents US $ 99,973.90.
En el presente trabajo de investigación se detalla la información de cada actividad a ejecutarse en el proyecto y así poder elaborar el presupuesto de obra de una vivienda unifamiliar de dos plantas planta baja y planta alta, con un área de construcción de 215,11 m², implantada en un área de terreno de 141.84 m² en el barrio Blanca García Álvarez de la ciudad de Machala. La finalidad de este trabajo de investigación es estimar el costo que tendría una vivienda unifamiliar de dos plantas, detallando cada actividad en la obra por medio del método unitario y así lograr estimar el presupuesto de nuestro proyecto. También para llevar a cabo nuestro proyecto, e s necesario conocer las especificaciones y normativas técnicas de construcción, para así, poder elaborar de manera adecuada los planos y para lograr nuestro objetivo, fue necesario el uso de una herramienta informática Microsoft Excel ya que nos facilitó el cálculo de nuestra memoria técnica en base a los planos ya diseñador y nos ayudó a organizar cada actividad que se iba realizando por en cada análisis de precios unitario, logrando obtener cada uno de nuestros rubros y obtener como resultado nuestro presupuesto aproximado del proyecto. Como resultado final de nuestro trabajo de investigación, tenemos que el presupuesto de nuestra vivienda de dos plantas ubicado en el barrio Blanca García Álvarez es aproximadamente de noventa y nueve mil novecientos setenta y tres dólares con 90 100 centavos U.S $99 973,90.
Keywords: COSTO; PRESUPUESTO; VIVIENDA UNIFAMILIAR; METODO UNITARIO